KEPEMIMPINAN PROFETIK DEBORA DALAM MENYOROTI PERAN PEREMPUAN SEBAGAI PEMIMPIN DI MASA KINI - Desri Patandianan; Herlin, Tety Ice Taruk Allo, Listra Tawang, Agustina (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
This article aims to examine Deborah's prophetic leadership as recorded in the Book of Judges chapters 4 and 5, and its relevance in encouraging the role of women as leaders today. Deborah, a female prophet and judge in a patriarchal social context, appears as an integrative leader: spiritual, strategic, and just. This study uses a qualitative-descriptive approach through a literature study method, with primary sources from the Bible and contextual and feminist theology literature. The discussion includes the figure of Deborah's prophetic leadership, the dimensions of spirituality and morality in her leadership, its relevance for women today, and the challenges and strategies to encourage women's leadership in the context of the church and society. The results of the study show that Deborah's story can be used as a theological basis to strengthen the legitimacy of women in Christian leadership. In addition, there needs to be a renewal in Biblical hermeneutics, theological education, and gender-just institutional policies so that women have equal space in answering the call to leadership. Deborah is a symbol that true leadership comes from a divine calling, not from social structures, and that women are capable of being prophetic, transformative, and contextual leaders